Lignin surface area influenced by biomass heterogeneity and pretreatment process - de Azevedo, Gabriel Oliveira [UNESP]; Shimizu, Felipe Lange [UNESP]; Fontes, Luciana Coelho [UNESP]; Contiero, Jonas [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2022)
Biomass conversion is challenged by the heterogeneity and lignin, a component that acts as a barrier to the enzymatic hydrolysis of polysaccharides. This study evaluated the effect of pretreatments on different fractions of sugarcane biomass lignin and cellulose exposure. Two different methods were used: dilute sulfuric acid (5%, 10%, and 20% w/w at 121 °C/30 min) and partial delignification with sodium chlorite (30% m/m at 70 °C/1 h) to reduce the exposed surface of lignin. The surface area of ​​lignin was obtained through the cationic dye Azure B, and cellulose access by enzymatic hydrolysis (15 FPU/g for 24 h—Cellic Cetec 2—Novozymes) was employed. Acid pretreatment was efficient in hemicellulose removal, and delignification removed lignin from all the biomasses fractions. Azure B dyes determined the surface area filled with lignin after dilute sulfuric acid pretreatment and partial delignification. The sample with the largest total surface area of lignin (52 m2/g of material) was the leaf pretreated with 5% sulfuric acid. The external fraction presented the largest specific surface area (240 m2/g) after partial delignification. These results indicate that reducing the lignin surface area enhances the glucose yield of enzymatic hydrolysis.
Keywords: Azure B; Cellulose accessibility; Diluted acid; Sugarcane biomass; Xylose